Mitigation of Salinity Stress Effects in Tomatoa (Lycopersicon esculentum Mill. ) by Using Calcium Chloride - Fadhil Alaywe Atiyah Al-Rubaiee (Nabatia, 2024)
In the world, salinity has become an increasing danger for agricultural production. A factorial pot experiment using a completely randomized design (CRD) was conducted in the present research, aimed to look at how growth, yield parameters, and biochemical contents were influenced by the exogenous application of calcium chloride (CaCl2, 0, 5, and 10 mM) of tomato exposed to salt stress (NaCl, 0, 25, and 75 mM), Growth was slowed and Both the sodium percentage and proline content increased under salt stress. However, the growth, yield, and biochemical content characteristics were improved by the application of Ca, enhanced plant height, dry weight of the shoots and roots, the number of fruits per plant, fruit weight, the percentage of nitrogen, calcium, magnesium, phosphorus, potassium, relative water content (RWC), and increased proline content, moreover a significant reduction in the sodium percentages, when compared to the control. Lastly, exogenous Ca use improves resistance to salt stress. Moreover, the use of 10 mM CaCl2 caused the beneficial effects of Ca, which has been suggested to enhance tomato performance in salinized conditions.